2012
DOI: 10.1523/jneurosci.5669-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Stable Functional Networks in Long-Term Human Electroencephalography

Abstract: Functional connectivity networks have become a central focus in neuroscience as they reveal key higher dimensional features of normal and abnormal nervous system physiology. Functional networks reflect activity-based coupling between brain regions that may be constrained by relatively static anatomical connections, yet these networks appear to support tremendously dynamic behaviors. Within this growing field, the stability and temporal characteristics of functional connectivity brain networks have not been wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
149
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 74 publications
(89 reference statements)
13
149
1
1
Order By: Relevance
“…A minimum of two minutes (range 122–199 seconds) of artifact-free recording from each patient was used for analysis. This epoch size has been previously demonstrated to be sufficient to produce high similarity between inferred functional networks within patients across different states of consciousness (Chu et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum of two minutes (range 122–199 seconds) of artifact-free recording from each patient was used for analysis. This epoch size has been previously demonstrated to be sufficient to produce high similarity between inferred functional networks within patients across different states of consciousness (Chu et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…We note that all of our reported results were qualitatively similar when using distance correction off, but the number of long distance structural connections identified was negligible without distance correction. Because proximal nodes are known to be highly connected in both structural and functional networks due to true anatomical and physiological connectivity as well as spatial bias in measurement techniques (Chu et al, 2012; Li et al, 2012), we report our results with distance correction on in order to highlight correlations between long distance structural and functional connections. Using the number of streamlines launched from the seed ROI and the number of voxels in the target ROI allows for calculation of a Connectivity Index (adapted from McNab et al, 2013): CI=false[Mean0.16667em#0.16667emof0.16667emdistance0.16667emweighted0.16667emstreamlines0.16667emthat0.16667emreach0.16667emthe0.16667emtarget0.16667emROI/total0.16667em#0.16667emof0.16667emstreamlines0.16667empropagated0.16667emfrom0.16667emseed0.16667emROIfalse].…”
Section: Methodsmentioning
confidence: 99%
“…Different epoch lengths and number of epochs are currently used in resting state functional connectivity studies, ranging from one second (Knyazeva et al , 2010, Chu et al , 2012) to a few minutes (Tahaei et al , 2012) or even a day (Kuhnert et al , 2010) for epoch length; and from one epoch (Ahmadlou et al , 2011) to over 100 epochs containing the entire EEG recording (Knyazeva et al , 2010). Previous studies have investigated epoch length in relation to connectivity stability (David et al , 2004, Honey et al , 2007, Chu et al , 2012 and showed that the length of epochs to obtain stable connectivity measures is highly dependent on the type of connectivity measure.…”
Section: Number and Length Of Epochs And Sample Frequencymentioning
confidence: 99%
“…Previous studies have investigated epoch length in relation to connectivity stability (David et al , 2004, Honey et al , 2007, Chu et al , 2012 and showed that the length of epochs to obtain stable connectivity measures is highly dependent on the type of connectivity measure.…”
Section: Number and Length Of Epochs And Sample Frequencymentioning
confidence: 99%
“…Indeed, the functional connectome (as described in a graph) is known to be dynamic (Bassett et al , 2011; Chu et al , 2012). However, it largely remains to be understood how the rich diversity of observed functional network dynamics are regulated.…”
Section: Dynamics and Diseasesmentioning
confidence: 99%